2013
DOI: 10.1124/jpet.113.205757
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Cardiovascular Pharmacology of 2′,3′-cAMP, 2′-AMP, and 3′-AMP in the Rat

Abstract: The naturally occurring purine 29,39-cAMP is metabolized in vitro to 29-AMP and 39-AMP, which are subsequently metabolized to adenosine. Whether in vivo 29,39-cAMP, 29-AMP, or 39-AMP are rapidly converted to adenosine and exert rapid effects via adenosine receptors is unknown. To address this question, we compared the cardiovascular and renal effects of 29,39-cAMP, 29-AMP, 39-AMP, 39,59-cAMP, 59-AMP, and adenosine in vivo in the rat. Purines were infused intravenously while monitoring mean arterial blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In this sense, CNPase represents as novel “energy” therapy target for heart failure beyond the traditional neurohumoral and hemodynamic modulation approaches. The CNPase-2′,3′-cyclic nucleotide system is present in the circulating system, and cardiomyopathy could increase the formation of 2′,3′-cyclic nucleotides through mRNA degradation [ 19 ]. AAV9-mediated CNPase myocardial expression alleviated the pressure overload-induced hypertrophic response and improved heart function ( Figure 3 and Figure 4 ), possibly by CNPase metabolizing 2′,3′-cyclic nucleotides into adenosine to exert beneficial physiological effects [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, CNPase represents as novel “energy” therapy target for heart failure beyond the traditional neurohumoral and hemodynamic modulation approaches. The CNPase-2′,3′-cyclic nucleotide system is present in the circulating system, and cardiomyopathy could increase the formation of 2′,3′-cyclic nucleotides through mRNA degradation [ 19 ]. AAV9-mediated CNPase myocardial expression alleviated the pressure overload-induced hypertrophic response and improved heart function ( Figure 3 and Figure 4 ), possibly by CNPase metabolizing 2′,3′-cyclic nucleotides into adenosine to exert beneficial physiological effects [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CNPase-2′,3′-cyclic nucleotide system is present in the circulating system, and cardiomyopathy could increase the formation of 2′,3′-cyclic nucleotides through mRNA degradation [ 19 ]. AAV9-mediated CNPase myocardial expression alleviated the pressure overload-induced hypertrophic response and improved heart function ( Figure 3 and Figure 4 ), possibly by CNPase metabolizing 2′,3′-cyclic nucleotides into adenosine to exert beneficial physiological effects [ 19 , 20 ]. Our study also explains the binding affinity of CNPase proteins with cyclic nucleotide positional isomers ( Figure 5 ), concluding that CNPase does not interfere with PDE 3′-5′-cyclic nucleotide pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine would reverse the initial event of microvascular ischemia induced by surgical trauma via vasodilatation through activation of adenosine receptors. Indeed, our recently published studies show that in vivo 2′,3′-cAMP causes vasodilation via activation of adenosine receptors [ 30 ]. In addition to vasodilation, 2′,3′-cAMP, via adenosine, stimulates the proliferation of vascular endothelial cells, which would accelerate vascular repair [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that administration of a non-cell-membrane permeable adenosine prodrug would provide more sustained levels in the abdominal cavity and would avoid potential toxicity on other organs. In this regard, our recent studies show that 2′,3′-cyclic adenosine monophosphate (2′,3′-cAMP), a positional isomer of 3′,5′-cyclic adenosine monophosphate (3′,5′-cAMP) and formed from the metabolism of mRNA, is metabolized extracellularly to adenosine by organ systems [ 21 30 ]. Because 2′,3′-cAMP is even more hydrophilic than 3′,5′-cAMP [ 31 ], the absorption of 2′,3′-cAMP would be limited because of lack of diffusion across cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…2',3'-cAMP was first detected in perfused rat kidney using liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) [ 17 ]. Additional studies have suggested that tissue injury triggers mRNA degradation, leading to production of 2',3'-cAMP that is converted through the action of the enzyme 2',3'-cyclic nucleotide phosphodiesterase to endogenous adenosine, which upon binding to various adenosine receptors can protect against acute organ injury, as well as have profound effects on the cardiovascular system [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Recently, 2',3'-cAMP and cGMP have been shown to correlate with leaf wounding stress in Arabidopsis , further suggesting that these nucleotides may be important in post-injury mechanisms [ 25 ].…”
Section: Introductionmentioning
confidence: 99%